ส่วนประสมการตลาดบริการที่มีผลต่อผู้บริโภคเจนเนอ เรชั่นวายในการใช้บริการคลินิกเสริมความงามในอำเภอเมืองเชียงใหม่ - บุษรินทร์ ภูวังหม้อ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The purpose of this independent study was to study the services marketing mix affecting of generation Y consumers towards selecting medical beauty clinics in Mueang Chiang Mai District. The results were as followed: Most of the respondents were single women, age between 32 – 37 years, educated at bachelor degree level with a salary between 10,001 to 15,000 Baht, and were familiar with Wuttisak Clinic. The first 3 medical beauty clinics that the respondents used the service were Medicare Clinic, Panipak Clinic, and Wuttisak Clinic. The medical beauty service that the respondents had used for the last 6 months were such as treatment of acid, ulcer, and scar including skin diseases. The respondents paid by cash with approximately 1,001 – 1,500 baht per time. The total amount of money that the respondents paid for the last six months was 3,000 Baht. The results was indicted that; Product factor affecting the overall respondents was in highest level. The first sub-factor with highest average was the professional image of the clinic. Price factor affecting the overall respondents was in highest level. The first sub-factor with highest average was the interesting package. Place factor affecting the overall respondents was in high level. The first sub-factor with highest average was the location should be easy to find. Promotion factor affecting the overall respondents was in high level. The first sub-factor with highest average was the location should be informed the information and promotion through letter, E-mail, Facebook, etc. People factor affecting the overall respondents was in high level. The first sub-factor with highest average was the professional doctor. Process factor affecting the overall respondents was in high level. The first sub-factor with highest average was the correctness of the service. Physical evidence factor affecting the overall respondents was in high level. The first sub-factor with highest average was the cleanliness of surrounding environment.